Factors affecting lower academic performance of grade 11 STEM students of ECT Excellencia Global Academy Foundation Inc. - Alan A. Bendanillo; April Rose Cansancio; Frances Monique Dungog; Mery Clare Quezon; Irish S. Rubin; Kisha Sermon (Science and Education, 2023)
This study aimed to determine the factors affecting the academic performance of grade 11 STEM students of ECT Excellencia Global Academy Foundation Inc. The factors affecting a student’s academic performance arise from several reasons. Accordingly, this study was done to identify the factors affecting the academic performance of grade 11 stem students, which may ultimately help in the improvement of both students and teachers. The students may gain from this research by being able to understand better the elements that may affect their academic performance. They might be able to improve their academic standing by using the findings that this investigation establishes. A quantitative research method was employed. The researchers primarily gathered the data for statistical analysis through which the specified survey questionnaires were distributed to the respondents in this research study. Average weighted mean was used to determine the level of impact of the different factors affecting the respondents’ academic performance.